Applicability of Tanaka & Johnston Analysis and Prediction of New Equation for Contemporary Nepalese Sample (Orthodontic Journal of Nepal, 2013)
Objective: To examine applicability of Tanaka & Johnston prediction in Nepalese sample. Materials & Method: A total of 100 samples of the age ranging from 14-24 years were selected for the measurement of mesio-distal widths of mandibular permanent incisors, and maxillary and mandibular permanent canines and premolars. Descriptive statistics was calculated and paired t-test was carried out to find the difference between predicted and actual values of canine and premolar mesio-distal widths. The linear regression equation was performed to develop new equation for Nepalese sample. Result: Mean differences were observed in actual and predicted values between the present study and the reports of Tanaka & Johnston. Coefficient of correlation was found for maxilla, r=0.52 and mandible, r =0.51. Conclusion: The equations and charts used for other ethnic sample do not accurately predict for Nepalese sample. The linear regression equation developed in this study can be used for orthodontic treatment for Nepalese patients.DOI: http://dx.doi.org/10.3126/ojn.v3i1.9269 Orthodontic Journal of Nepal, Vol.3, No.1, 2013: 14-18